KESANTUNAN BERBAHASA PADA FORUM SEMINAR DESAIN PENELITIAN MAHASISWA PROGRAM STUDI BAHASA INDONESIA FKIP UNIVERSITAS TANJUNGPURA PONTIANAK - Vira Ameiliya; Laurensius Salem; Mellisa Jupitasari (Universitas Tanjungpura, 2021)
abstrakThis study aims to increase the reader’s understanding of language politeness at the research design seminar forum for students of the Indonesia language education study program FKIP Tanjungpura Universitas Pontianak. This research is in the form of qualitative with descriptive method. The source of the date for this research is a vidio via google meet and the student research design seminar forum for students of the Indonesian language education study program FKIP Tanjungpura University Pontianak. Researchers choose a research design seminar forum for students of the Indonesian language education study program FKIP Tanjungpura University Pontianak. The result of the study in this study contained 35 unterance, the maxim of generosity 5 utterances, maxim of sympathy 1 utterance, maxim of appreciation 7 utterances, maxim of wisdom 14 utterances, maxim of simplicity 3 utterances, and maxim of consensus 4 utterances. The implementation of the learning outcomes of this research is combined with Indonesian language learning in class 10 old semester at the high school level/equivalent in the 2013 curriculum with KD 3.3 Analyzing the structure, content problems of argumentation, knowledge, and recommendations) linguistics of the expository texts that are heard and read. 4.3 Analyzing the structure and language of the exposition text.Keywords: language politeness, maxim context, eksposisi text.